The Integration of Flipped Teaching with the Support of Online Platforms - Flores Silva, Luis Enrique; Pimienta Rosales, Verónica (Verbum et Lingua: Didáctica, lengua y cultura, 2024)
The integration of Flipped teaching in language learning seems to be an appealing option to maximize class time and address students’ learning needs and interests. On this premise, an action research study was carried out to explore the influence of Flipped methodology in the development of oral skills. Data obtained from this particular teaching context suggest that students exhibited better score results in oral structure, fluency being the one with the lowest score results. Although the results from the experimental group were not the expected ones, individual score results show that the most motivated students towards Flipped lessons obtained better results in areas corresponding to oral fluency, being that particular area the one identified as the weakest feature prior the study. In addition, daily class observations conducted to identify students´ attitudes and reactions towards Flipped methodology were found to be valuable since they provided information that may be useful to consider before implementing Flipped learning, and hence ensure better practices and results.